JAVENGLISH (WHEN JAVANESE SPEAK ENGLISH WITH A JAVANESE ACCENT): AN ANALYSIS OF SOCIAL MEDIA POSTS - Fitria, Tira Nur (Widyaparwa, 2023)
An accent is a way of pronouncing something unique in a particular language, and specific to a country, region, or social class. Recently, the 'Javanese accent' trend has been buzzing on social media. The viral Java accent began when a content creator from Surabaya, East Java, made a video that featured Javanese accents in several words. This research investigates the phenomenon of Javenglish which occurs when Javanese people speak English with a Javanese accent in Instagram Reels @natkenira. This research employs a descriptive qualitative approach. The analysis shows that 60 English words from 7 Reels videos are pronounced with a Javanese accent. Indonesian speakers of English can be influenced by the accent/dialect of their mother tongue when speaking English. This causes variations of letter sounds, both consonants and vowels. Javanese style in speaking English is sometimes related to the “medok” accent as the most recognizable characteristic of the Javanese language. This character may be difficult to remove because of genetic inheritance. An accent is a characteristic form distinctive by pronunciation, style, and features of a certain language often linked with certain social groups, usually, people hope members and groups of this social language use style or speech characteristics. There are 60 words with Javenglish pronunciation in the social media content of Instagram Reels @natkenira. Similar research is still possible to conduct and can provide input for this research. In further research, the number of research subjects can be added to get maximum results. Baru-baru ini, tren 'aksen Jawa' sedang ramai di media sosial. Awal mula viralnya aksen Jawa adalah ketika seorang content creator asal Surabaya, Jawa Timur membuat video yang menampilkan aksen Jawa dalam beberapa kata. Penelitian ini menyelidiki fenomena Javenglish (ketika orang Jawa berbicara bahasa Inggris dengan Aksen Jawa) di Reels Instagram @natkenira. Penelitian ini bersifat deskriptif kualitatif. Analisis menunjukkan bahwa 60 kata bahasa Inggris dari 7 video Reels diucapkan dengan aksen Jawa. Penutur bahasa Inggris Indonesia dapat dipengaruhi oleh aksen/dialek bahasa ibu mereka dalam berbicara bahasa Inggris. Hal ini menyebabkan variasi bunyi huruf baik konsonan maupun vokal. Gaya bahasa Jawa dalam berbicara bahasa Inggris terkadang dikaitkan dengan aksen “medok” sebagai ciri khas bahasa Jawa yang paling mudah dikenali. Karakter ini mungkin sulit dihilangkan karena pewarisan genetik. Aksen adalah suatu bentuk ciri yang khas melalui pelafalan, gaya, dan ciri-ciri bahasa tertentu yang sering dikaitkan dengan kelompok kelompok sosial tertentu, biasanya orang berharap anggota dan kelompok sosial ini menggunakan gaya atau ciri tutur. Aksen sebagai cara mengucapkan sesuatu yang unik dalam bahasa tertentu, dan khusus untuk suatu negara, wilayah, atau kelas sosial. Terdapat 60 kata yang mengandung Javenglish di media sosial Reels Instagram @natkenira. Penelitian serupa masih dimungkinkan untuk menambah dan memberikan masukan bagi penelitian ini. Pada penelitian selanjutnya, jumlah subjek penelitian dapat ditambah untuk mendapatkan hasil yang maksimal.